The Implementation Of Presidential Regulation Number 148 Of 2015 In The Construction Of Lubuk Linggau–Curup–Bengkulu Toll Road - Meli Satri; Harius Eko Saputra; Yusuarsono Yusuarsono (UNIVED PRESS, Universitas Dehasen Bengkulu, 2022)
This study aims to determine the success rate of the implementation of Presidential Regulation Number 148 of 2015 in the construction of Lubuk Linggau–Curup–Bengkulu Toll Road through analysis of data and information obtained in the field. The limitation of the problem in this research focuses on the construction of Lubuk Linggau–Curup–Bengkulu Toll Road Bengkulu-Taba Penanjung segment. This study uses Edward III's theory of policy implementation using descriptive qualitative research methods. Data were collected using observation, interviews and documentation. Based on the results of this study, it is known: (1) Communication: The implementation of Presidential Regulation No. 148 of 2015 in the construction of Bengkulu-Taba Penanjung toll road has been running according to existing regulations. (2) Resources: Human resources in implementing the land acquisition policy in the construction of Bengkulu-Taba Penanjung toll road are sufficient. (3) Disposition: As the implementation of the policy, the land acquisition committee supports Bengkulu-Taba Penanjung toll road development policy and tries to carry out its duties well. However, there are residents who show an attitude of not supporting the existence of development activities on the grounds that the amount of compensation received is not appropriate. (4) Bureaucratic Structure: The bureaucratic structure can simplify and balance the actions of policy implementers in carrying out their respective duties according to their respective fields. Overall everything is in accordance with the rules and is going well, the existing obstacles can be resolved and the development process can be carried out as it should.